Pengembangan Media Flash Card Berbasis Qr-Code Pada Materi Gerhana Untuk Meningkatkan Hasil Belajar IPA (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2023)
This study aims to determine how to develop qr-code-based flash card media, determine the feasibility of qr-code-based flash card media, determine the level of practicality of the media, determine student responses to the use of qr-code-based flash card learning media. This research is a type of research and development using the 4D model. Based on the analysis of the needs of teachers and students, it can be concluded that students need audio-visual based media that the researchers developed in the form of qr-code based flash cards. Flash card learning media based on qr-code was validated by media experts and material experts. Learning media was tested in a limited way on 8 students and field tested on 21 grade VI students at SDN 3 Krasak Pecangaan. Flash card media based on qr-code is generated through the stages of define, design, development and disseminate. The results of the qr-code based flash card media validation test were tested by 2 media experts obtaining a score of 3.1 in the feasible category and 3.6 in the very feasible category. According to material experts, a score of 3.7 was obtained with a very decent category. Meanwhile, for the level of practicality, the media obtained a score of 3.7 in the very practical category. Student responses to qr-code-based flash card media obtained a score of 3.39 in the very good category. Then in the media effectiveness test using the paired sample t-test it is known that the acquisition of tcount 6.086 > ttable 1.895 so that there is a significant difference in the limited trial while in the field trial there is a result of tcount 9.485> ttable = 1, so there is a significant difference in the test try so that there are significant differences in field trials before and after using Qr-Code-based Flash Card Media in class VI students of SD N 3 Krasak Pecangaan.